PENGARUH KOMPETENSI, INDEPENDENSI, DAN PROFESINALISME AUDITOR TERHADAP KINERJA AUDITOR DENGAN ETIKA PROFESI SEBAGAI VARIABEL MODERATING (Studi pada Kantor Akuntan Publik di Pekanbaru, Batam, dan Medan) - Alnoprika Muluk; Zirman -; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research examines the effect of competence, independency, and professionalism in auditors performance with an ethic of profession of moderating variable. The respondents in this research are auditors whom work in public accounting office in pekanbaru, batam and medan. The Amount of auditors that has been visited are 145 auditors from 29 public accounting offices. The method of sample determining is purpossive sampling method,meanwhile the method of data tabulation has been used by researcher is doubled regression and moderate regression analysis. The result shows that competence, independency, and professionalism influence significantly to auditors performance. The ethic of profession can be a moderate variable for professionalism, but it can't be a moderate variable for competence and independency.Keywords: competency, independency, professionalism, ethics, auditor performance.